Use of a corneal impression membrane and PCR for the detection of herpes simplex virus type‐1. Issue 9 (September 2019) - Brunner, Matthias; Somerville, Tobi; Corless, Caroline E.; Myneni, Jayavani; Rajhbeharrysingh, Tara; Tiew, Stephanie; Neal, Timothy; Kaye, Stephen B.
N/A: Purpose. : To investigate the use of a corneal impression membrane (CIM) for the detection of herpes simplex virus type 1 (HSV‐1) in suspected herpes simplex keratitis (HSK). Methodology. : In the laboratory study, swabs and CIMs made from polytetrafluoroethylene were spiked with different concentrations of HSV‐1. DNA was extracted and real‐time PCR undertaken using two sets of primers. In the clinical study, consecutive patients presenting with suspected HSK were included. For each patient, samples were collected from corneal lesions with a swab and a CIM in random order. Clinical details were collected using a standardized clinical form and patients were categorized into probable, presumed and possible HSK. Results. : There was no difference in the performance of both primer sets for all HSV‐1 dilutions ( P =0.83) using a CIM or between a CIM and a swab ( P =0.18). In total, 110 patients were included. Overall, 73 patients (66.4 %) had probable, 20 patients (18.2%) presumed and 17 patients (15.5%) possible HSV‐1 keratitis. The HSV‐1 detection rate was significantly higher using a CIM (40/110, 36.4%) than a swab (28/110, 25.5%) ( P =0.004). In the probable HSV keratitis group, the detection rate using a CIM was 43.8% compared to 27.4% for a swab ( P =0.004). The cycle threshold values obtained for the conjunctival swabs were higher than those obtained for the CIMs ( P <0.001). Conclusions. : In suspected HSK, a CIM is a useful alternative to a swab and more likely to detect the presence of HSV‐1.